Conceptualization of Drug Metaphors in YouTube News - Saputro, Ahmad Nur’aini; Suhardi, Suhardi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to reveal the conceptualisation of drug metaphors in YouTube news. This type of research includes qualitative research which is descriptive analysis. This research method uses the methods of listening, engaging, and discoursing. The advanced technique uses the comparative equating technique to determine the correspondence between metaphorical expressions and the cognitive function of metaphors. The results of this study reveal that ontological metaphors are more dominant in YouTube news compared to structural metaphors and orientational metaphors. The narrator conceptualises more physical things for abstract things. The metaphors contained in the drug news were found to be 2 structural metaphors, 3 orientational metaphors, and 12 ontological metaphors.